THE STRATEGY OF THE MINISTRY OF TOURISM IN THE DEVELOPMENT OF TOURIST DESTINATIONS IN THE DISTRICT OF SAMOSIR THROUGH THE BRAND IMAGE OF THE CITY - GRACE MIRANDA ROMAITO SITORUS; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2021)
This research is motivated by the many problems of Pariwasata in Samosir Regency that have not been developed. This is due to the tourism potential, which amounts to 115. However, in reality, the potential of Samosir Regency, the Samosir Tourism Office, has not done the distribution of tourism development properly. Each tourist attraction and service is still very limited, even though tourists really expect extra services to provide satisfaction to their tourists. Therefore, the purpose of this study is to describe and analyze the strategies undertaken by the Ministry of Tourism in Developing Tourism Destinations in Samosir Regency through city branding. This study uses the analysis method of Strength, Weakness, Opportunity, Treath (SWOT) and a qualitative descriptive approach with primary and secondary data types obtained from observations and interviews and direct observation.